Estimation Method of Carbon Emissions in the Embodied Phase of Low Carbon Building - Hongwei Liu; Jun Li; Yafei Sun; Yanshu Wang; Haichun Zhao (Advances in Civil Engineering)
The carbon emission at the embodied phase is a complex combination, extending the life cycle of the building, defining the process of the embodied phase scientifically and finding out the direct and indirect carbon emission sources in the embodied phase. Building materials have the characteristics of “low carbon surface, hidden high carbon.” Emission factor calculation method is used to establish carbon emission model for building materials. Considering the effect of design optimization on the carbon emissions of the whole life cycle of the building, a low carbon level system is set up to optimize the target of low carbon design. In the construction phase, the carbon emission sources, emission boundary, and calculation model are determined according to the subdivisional engineering division method. Through a series of process decomposition, the total amount of carbon emissions at the embodied phase can be obtained, and the carbon emission quota list at the embodied phase can be compiled to provide technical support for the carbon trading mechanism of the building.